Experimental isolation and preservation of solid organs before transplantation: effects of pretreatment using four different molecules. Issue 6 (June 2020) - Chalasti, Maria; Iordanou, Christos; Kratiras, Zisis; Stylianaki, Aikaterini; Trigka, Eleni-Andriana; Lakiotaki, Eleftheria; Makedou, Kali; Iliadis, Stavros; Zografos, Konstantinos G.; Dimitroulis, Dimitrios; Chrisofos, Michail; Patsouris, Efstratios; et al.
Objectives: In transplantation surgery, the ischaemic organ and reperfusion impairment after cold storage remains a considerable risk factor for impaired function and potential failure of the grafted organ. Substantial logistical efforts have been undertaken to reduce the cold ischaemic time because the demand for available transplant organs and the periods of cold ischaemia are increasing. Methods: Four molecules were investigated (erythropoietin, sildenafil, lazaroid [U74389G], octreotide) in individual intravenous infusions 1 hour before the organ was harvested. This study was performed in 30 healthy landrace/large-white pigs (male; >10 weeks old; average weight, 22 ± 2 kg) in groups of six. The organs were studied at harvest, and at 8 and 24 hours post-harvest. Results: The lazaroid molecule increased malondialdehyde (MDA) levels in the liver and pancreas at 8 hours. Hepatic lazaroid molecules improved liver histology at 8 and 24 hours. For kidneys, erythropoietin had a positive effect at 24 hours post-harvest. For the pancreas, octreotide showed better performance. In the lungs, there was less interstitial oedema with erythropoietin and lazaroid compared with the control group at 8 hours post-harvest. Conclusion: All molecules had a positive effect and decreased ischaemia/reperfusion graft injury. Thus, pretreatment before organ harvest has a beneficial role.